Noninvasive evaluation of hepatic fibrosis in hepatitis C virus‐infected patients using ethoxybenzyl‐magnetic resonance imaging. Issue 6 (22nd May 2013) - Nojiri, Shunsuke; Kusakabe, Atsunori; Fujiwara, Kei; Shinkai, Noboru; Matsuura, Kentaro; Iio, Etsuko; Miyaki, Tomokatsu; Joh, Takashi
Abstract Background and Aims Liver biopsy is the gold standard test to determine the grade of fibrosis, but there are associated problems. Because gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid is secreted partially in hepatocytes and bile, it is possible that ethoxybenzyl‐magnetic resonance imaging (EOB‐MRI) correlates with liver function and liver fibrosis. The aim of this study was to compare the fibrosis seen in liver biopsy samples to the signal intensity of the hepatobiliary phase measured on EOB‐MRI in hepatitis C virus (HCV)‐infected patients. Methods Two hundred twenty‐four (estimation 149, validation 75) HCV‐infected patients with histologically proven liver tissue who underwent EOB‐MRI were studied. Overall, fibrosis staging was 15/24/19/46/45 for F0/F1/F2/F3/F4, respectively. A 1.5‐Tesla magnetic resonance system was used, and the regions of interest of the liver were measured. Four methods were used: (i) relative enhancement: (post‐enhanced signal intensity [SI] − pre‐enhanced intensity)/pre‐enhanced intensity; (ii) liver‐to‐intervertebral disk ratio (LI): post‐enhanced (liver SI/interdisc SI)/pre‐enhanced (liver SI/inter disc SI); (iii) liver‐to‐muscle ratio: post‐enhanced (liver SI/muscle SI)/pre‐enhanced (liver SI/muscle SI); and (iv) liver‐to‐spleen ratio: post‐enhanced (liver SI/spleen SI)/pre‐enhanced (liver SI/spleen SI). Results To discriminate F0‐1 versus F2‐4 or F0‐2 versus F3‐4 or F0‐3 versus F4, LI at 25 min (LI25) had the highest area under receiver operating characteristic (0.88, 0.87, and 0.87, respectively) in these four methods and also in the validation set. Conclusion LI at 25 min seems to be a useful method to determine the staging of fibrosis as a non‐invasive method in HCV‐infected hepatitis or cirrhosis patients.